Reduced gland mucin‐specific O‐glycan in gastric atrophy: A possible risk factor for differentiated‐type adenocarcinoma of the stomach. Issue 10 (October 2015) - Yamada, Shigenori; Okamura, Takuma; Kobayashi, Satoshi; Tanaka, Eiji; Nakayama, Jun
Abstract Background and Aims O‐glycans exhibiting terminal α1, 4‐linked N‐acetylglucosamine (αGlcNAc) are attached to MUC6 in gastric gland mucins and serve as a tumor suppressor for gastric adenocarcinoma. Gastric atrophy is associated with risk for gastric cancer. However, the significance of αGlcNAc expression in pyloric glands of chronic atrophic gastritis remains unknown. Here, we asked whether reduced αGlcNAc expression in chronic atrophic gastritis is associated with risk for gastric cancer. Methods We quantitatively analyzed expression of αGlcNAc relative to MUC6 in pyloric glands by immunohistochemistry in 67 patients with normal mucosa, 70 with chronic atrophic gastritis, 68 with intramucosal differentiated‐type adenocarcinoma, and 11 with intramucosal undifferentiated‐type adenocarcinoma. We also compared the Ki‐67 labeling index in gastric epithelial cells between chronic atrophic gastritis and normal gastric mucosa with respect to αGlcNAc reduction. Results In normal pyloric mucosa, αGlcNAc was co‐expressed with MUC6. By contrast, in chronic atrophic gastritis, pyloric gland αGlcNAc expression was significantly reduced relative to MUC6. In intramucosal gastric cancer, αGlcNAc expression in pyloric glands found just beneath differentiated‐type adenocarcinoma was also reduced relative to MUC6. However, pyloric glands present beneath undifferentiated‐type adenocarcinoma exhibited no αGlcNAc decrease. The Ki‐67 labeling index in chronic atrophic gastritis showing αGlcNAc reduction was significantly increased relative to that in normal gastric mucosa. Conclusions Because αGlcNAc prevents the gastric cancer development, reduced αGlcNAc expression in chronic atrophic gastritis is a possible risk factor for differentiated‐type adenocarcinoma of the stomach.